The complete degradation of acetanilide by a consortium of microbes isolated from River Maros - Hatvani, Lóránt (Acta Biologica Szegediensis, 2013)
Chemical pollutants occurring in rivers may have severe effects on human health along with being harmful to the environment. Bioaugmentation is a potential tool for the removal of xenobiotics from soil and water therefore the objectives of this study were the isolation, identification and characterization of microbes with acetanilide- and aniline-degrading properties from the River Maros. Microbes isolated on minimal media containing acetanilide or aniline-HCl as a sole carbon and nitrogen source were considered as acetanilide- or aniline-degraders. The decomposition of acetanilide and aniline were followed by High Pressure Liquid Chromatography (HPLC). An acetanilide-degrading bacterium, identified as Rhodococcus erythropolis, was able to convert acetanilide to aniline, which was further decomposed by the fungal isolate Aspergillus ustus when the two microbes were co-cultivated in a minimal medium containing acetanilide as a sole carbon and nitrogen source. The strains isolated in this study might be used in approaches addressing the biodegradation of acetanilide and aniline in the environment.